Os caminhos da pragmática no Brasil - Rajagopalan, Kanavillil (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
This paper traces the history of the study of pragmatics in Brazil. It is shown that Brazilian researches have, by and large, remained attentive to major developments in the field taking place elsewhere in the world. Of particular importance is the burgeoning tendency to focus attention on social issues affecting the day-to-day lives of ordinary people. More and more researchers are realizing the need to assume a critical role in relation to the theories they encounter in the literature.